Contextual Determinants of Effective Curriculum Implementation in Nigeria (2023)
This study was designed to investigate the impact of big five personality traits on the academic performance of undergraduate in southwest geo-political zone of Ibadan. The research design adopted is descriptive research design of correlational type. Three thousand (3000) participants were chosen from the population using stratified random sampling. Three research questions were raised for the study. A structured questionnaire consisting of a demographic section (including CGPA) and measures of big five personality traits were used to collect data. Data collected were analysed through the use of Pearson Product Moment Correlation and Multiple Regression Analysis all were tested at α = 0.05 level of significance. The findings revealed that there were significant relationships between openness (r = 0.455, p < 0.05), conscientiousness (r = 0.324, p < 0.05), extroversion (r = 0.217, p < 0.05), agreeableness (r = 0.270 p < 0.05), neuroticism (r = 0.694, p < 0.05) and academic performance of undergraduate students. All the independent variables (big five personality traits) jointly accounted for 58.4% (Adj. R2 = 0.584) of the total variance in determining students’ academic performance. The independent variables made a relative significant contribution to academic performance in the following order: conscientiousness (β = 0.175, t = 3.599, p < 0.05); agreeableness (β = 0 .220, t = 4.689, p < 0.05) and neuroticism (β = 0.607, t = 8.090, p < 0.05). However, the following are not significant predictors of academic performance among undergraduates: openness (β = 0.063, t = 1.117, p > 0.05) and extroversion (β = 0.062, t = 1.218, p > 0.05). The study found that personality traits, such as conscientiousness, agreeableness, and neuroticism significantly and positively impact academic performance. Therefore, the researcher concluded that students with possesses the following personality traits are more likely to excel well academically viz conscientiousness, agreeableness, neuroticism openness and extroversion personality traits. Since all and educators should focus on teaching methodologies that cater to the needs of the students. Additionally, all stakeholders should work towards creating an environment that supports the growth and development of these traits in students.